2008
DOI: 10.1103/physrevc.77.015805
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarized asymmetric nuclear matter and neutron star matter within the lowest order constrained variational method

Abstract: In this paper, we calculate properties of the spin polarized asymmetrical nuclear matter and neutron star matter, using the lowest order constrained variational (LOCV) method with the AV 18 , Reid93, U V 14 and AV 14 potentials. According to our results, the spontaneous phase transition to a ferromagnetic state in the asymmetrical nuclear matter as well as neutron star matter do not occur.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…In the same spirit, a detailed study of sum rules can enlighten the contribution of the tensor for various physical situations (see for instance [20]). Finally, applications to pure neutron matter is of great importance (see for instance [45][46][47][48][49][50][51][52][53][54][55][56][57]) and will be the subject of a forthcoming article in preparation. In that case, the above formulae are no longer directly usable and have been adapted to that specific case.…”
Section: Discussionmentioning
confidence: 99%
“…In the same spirit, a detailed study of sum rules can enlighten the contribution of the tensor for various physical situations (see for instance [20]). Finally, applications to pure neutron matter is of great importance (see for instance [45][46][47][48][49][50][51][52][53][54][55][56][57]) and will be the subject of a forthcoming article in preparation. In that case, the above formulae are no longer directly usable and have been adapted to that specific case.…”
Section: Discussionmentioning
confidence: 99%
“…In our calculations, the equation of state of hot nucleonic matter is determined using the lowest order constrained variational (LOCV) method as follows [9][10][11][12][13][14][15][16]. We adopt a trail wave function as…”
Section: A Hadron Phasementioning
confidence: 99%
“…In these works microscopic calculations employing the LOCV method with realistic nucleon-nucleon potentials were used. We also calculated the energy per particle and other properties of polarized asymmetric nuclear matter [49] and polarized neutron star matter [49] by using the LOCV method and parabolic approximation. We concluded that a spontaneous phase transition to the ferromagnetic state in these types of matter does not occur.…”
Section: Introductionmentioning
confidence: 99%